(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The vehicles are controlled by the lower extremities of the automotive suspension systemlocated at the front. The primary aim of this study is to evaluate the structural integrity of the lower controlarm under specific loading conditions using finite element analysis techniques. The ANSYS simulationsoftware is utilized for conducting Finite Element Analysis (FEA) simulations and modeling of the lowercontrol limb. The finite element analysis (FEA) simulation yielded significant results, including contourdiagrams that visually represented deformation, equivalent stress, and shear stress. The arm’s cornerregion exhibited the maximum equivalent stress magnitude, measuring 153 MPa, in contrast to the supportregion which experienced the minimum stress level.